從十二年國教核心素養探究中小學體育類科師資合流培育之可能 Physical Education Teacher Cultivating System and Curriculum Planning for the 12-Year Basic Education in Taiwan - 林玫君 Mei-Chun Lin; 蔡明學 Ming-Hsueh Tsai; 范信賢 Hsin-Hsien Fan; 陳儷今 Li-Chin Chen (National Taiwan Normal University, 2020)
本研究旨在評估臺灣中小學體育師資合流培育政策之可行性，並以《十二年國民基本教育課程綱要》為核心，探究中小學體育類科師資培育課程規劃。本研究以問卷調查進行，調查對象為全國中小學各校體育組長，共 3,407 份有效問卷，並輔以五場次 22 人次的焦點訪談 等方式，質量並進的方式分析。本研究認為：一、我國中小學體育師資合流培育機構單位足以因應現場需求，然就制度面應從學生修課學分數進行調整；二、教育專門課程應結合素養的發展方向，特別在溝通互動素養相關能力如何轉化至體育教學層面仍需努力；三、中小學 體育教師在課程實踐方展方向上有若干差異；四、師培機構在體育專門課程設計與課程實施有其調整之空間。最後，研究者依據研究結論提出相關建議，以作為《十二年國民基本教育課程綱要總綱》實施後，中央教育主管機關對於中小學體育類科教師合流培育政策實施之參 考依據。 This study evaluated the feasibility of the policy of merging the faculty of physical education into primary and secondary schools in Taiwan. Additionally, it explored the curriculum planning for training physical education teachers in primary and secondary schools following the recommendations of the 12-year basic education curriculum. The study was conducted through a questionnaire survey, with a total of 3,407 valid responses. The survey respondents were the heads of the sports teams of their schools. The survey was supplemented by 22 focus interviews conducted during five different occasions, and the quality was analyzed following a consistent method. The study presented the following ideas: (1) Taiwan's primary and secondary school's physical education faculty cultivation institutions are sufficient to meet the needs of the current education system; however, the system should be adjusted according to the student's course scores. (2) The specialized curriculum should be combined with literacy's development direction, especially in the field of communication. A method to integrate interpersonal literacy-related abilities into the physical education level is still required. (3) There are some differences between the direction of curriculum practices of primary and secondary school physical education teachers. (4) The training institutions should adjust their curriculum design and curriculum implementation.